Self-esteem Changes of Third Culture Kids When Havruta Discussion Reading Therapy Classes Were Applied - jong-sik ko (Pan-African Journal of Health and Environmental Science)
Background: Cultural attachments among third culture kids (TCKs) are indefinite because of frequent encounters with different cultural environments. This study was concerned with the changes in the self-esteem of TCKs when havruta discussion reading therapy classes were conducted.